Effect of Research Engagement on EFL Teachers' Motivation for and Efficacy in Teacher-Research - Boran, Gorsev Sonmez (TURKISH EDUCATION ASSOC, 2018)
The purpose of this study is to investigate whether research engagement helps participating teachers develop as motivated and efficacious teacher-researchers. Seventeen non-native English as a Foreign Language (EFL) teachers participated in the study. The study specifically aimed to examine if there are any differences in participants' motivation for research and efficacy in research at the end of the INSET course. Data came from Motivation for and Efficacy in Research questionnaires which were originally developed for the purposes of this study and other sources (i.e. interviews, essays). The findings of the study indicated that even though the participants' efficacy for research engagement increased significantly, the instruction did not elicit any statistically significant changes in their motivation levels. Results also revealed significant implications for teacher educators, EFL teachers, teacher education departments and MA programs.
Keywords: Teacher-research; Motivation; Efficacy; In-service teacher education